The Takrir Method in Improving Qur’an Memorization Among Students at Rumah Qur’an Maskanul Muttaqin, Muaro Jambi Village - Solehah, Martus; Mohd Arifullah; M. Syarhan Jailani (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study aims to describe the implementation of the takrir method, identify the factors influencing its success, and analyze its effectiveness in enhancing students’ memorization. This study is motivated by the importance of applying the takrir method in strengthening and improving Qur’an memorization among students at Rumah Qur’an Maskanul Muttaqin. Although the takrir method has been implemented as the main strategy in the tahfidz program, its application has not been fully optimal, as indicated by several students who have not yet reached their targeted memorization goals. This research employs a descriptive qualitative approach, utilizing observation, interviews, and documentation as data collection techniques. Data were analyzed through data reduction, data presentation, and conclusion drawing, with data validity ensured through source triangulation and persistent observation. The findings indicate that the takrir method is implemented in a scheduled and structured manner as part of daily activities; however, its effectiveness varies due to differences in students’ discipline, motivation, and time management, particularly among university-level students. Supporting factors include internal motivation, discipline, teacher competence, and institutional support, while obstacles involve limited time and additional academic responsibilities. Overall, the takrir method contributes positively to strengthening memorization and encouraging consistent revision. This study contributes to a better understanding of the takrir method in nonformal tahfidz institutions, highlighting both theoretical insights and practical guidance. It demonstrates that the method can be effective when supported by strong institutional guidance, capable instructors, and high student motivation, providing a reference for enhancing memorization strategies among students with diverse academic and personal responsibilities.